1998
DOI: 10.1021/ma9715839
|View full text |Cite
|
Sign up to set email alerts
|

Interpolymer Complexation between Poly(N-methyl-4-piperidinyl Methacrylate) and Acidic Polymers

Abstract: Polymer complexes of a basic polymer, poly(N-methyl-4-piperidinyl methacrylate) (PMPMA), with a weak acidic polymer poly(p-vinylphenol) (PVPh), and strong acidic polymers such as poly(acrylic acid) (PAA), poly(methacrylic acid) (PMAA), poly(styrenesulfonic acid) (PSSA), and poly(vinylphosphonic acid) (PVPA), have been prepared by mixing ethanol/H2O (1:1) solutions of the respective components. The complexes were examined by Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…Upon the formation of complexes, the N 1s spectra become broader and asymmetric, and each can be deconvoluted into three component peaks, with two of them remaining at the same positions and the third one appearing at 400.9 eV. We have earlier shown that when the nitrogen atoms of pyridine and piperidine groups are protonated, the binding energy of N 1s electrons is raised by 2.0 -2.4 eV 33,35) . Apparently, it is the N(3) in PVI that is protonated.…”
Section: Xps Characterizationmentioning
confidence: 98%
“…Upon the formation of complexes, the N 1s spectra become broader and asymmetric, and each can be deconvoluted into three component peaks, with two of them remaining at the same positions and the third one appearing at 400.9 eV. We have earlier shown that when the nitrogen atoms of pyridine and piperidine groups are protonated, the binding energy of N 1s electrons is raised by 2.0 -2.4 eV 33,35) . Apparently, it is the N(3) in PVI that is protonated.…”
Section: Xps Characterizationmentioning
confidence: 98%
“…The complexation between PYEAF and PSSA or PVPA gives 80 -90% yield, while that between PYEAF and PMAA gives just about 10% yield. The yields of the complexes appear to be related to the acidity of the polymers, as the pH values of 0.10 M ethanol/water (1 : 1 v/v) solutions of PSSA, PVPA, PAA and PMAA have been reported to be 1.36, 2.33, 3.04 and 3.57, respectively 20) . Furthermore, the fractions of protonated nitrogen in the complexes, as determined by XPS, also follow the order PYEAF/PSSA A PYEAF/PVPA A PEAF/PAA A PYEAF/PMAA, and this will be further mentioned later.…”
Section: Formation Of Complexesmentioning
confidence: 99%
“…Thus, the surface composition can be substantially different from the bulk composition. In most cases, the composition of a polymer complex depends on the feed composition, and it can be very different from the feed composition 6,13,14,20) . Similarly, the surface composition of a PYEAF/polymer complex is different from the feed composition, except for two PYEAF/ PSSA complexes.…”
Section: Formation Of Complexesmentioning
confidence: 99%
“…The nature of the solvent, 18 -24 the composition, 25,26 and the density of the functional groups of one or both polymers 12,26 -30 affect the formation of interpolymer complexes.…”
Section: Viscometry Analysismentioning
confidence: 99%